Characterization of the binding motif for the T3SS master regulator LcrF in Yersinia pseudotuberculosis. Issue 6 (11th March 2021) - Liu, Luyi; Huang, Shaojia; Fei, Keke; Zhou, Wei; Chen, Shiyun; Hu, Yangbo
ABSTRACT: LcrF is the master regulator that positively regulates the Ysc type III secretion system (T3SS) in Yersinia and shares a high similarity with the DNA-binding domain of the T3SS master regulator ExsA in Pseudomonas aeruginosa . Based on these features, bioinformatics analysis has predicted a putative LcrF-binding site in its target promoters. Here, we experimentally characterized its binding motif. An adenine-rich LcrF-binding region in the lcrG promoter sequence, a typical regulatory target of LcrF, was first confirmed. To obtain detailed information, this binding region was cloned into a synthetized promoter and mutations in this region were further constructed. We demonstrated that the 5'-AAAAA-n5 -GnCT-3' sequence is required for LcrF regulation and this motif is strictly located 4-bp upstream of a noncanonical promoter, in which the -35 and -10 elements are separated by a 21-bp spacer. Consistently, the putative binding motif was found in promoters of nine T3SS related operons or genes positively regulated by LcrF. Transcriptome analysis further confirmed that LcrF specifically activates T3SS genes in Yersinia . Collectively, our data suggest that LcrF has evolved to be a specific T3SS activator with a stringent sequence requirement for transcriptional regulation. Abstract : The master regulator LcrF specifically activates Yersinia T3SS genes by recognizing the 5'-AAAAA-n5 -GnCT-3' sequence 4-bp upstream of uncanonical 21-bp spacer promoters.